Hypercephalinemia and Experimental Venous Thrombosis in the Rat - Nordöy, Arne F (Thrombosis and Haemostasis, 1964)
Nine, 18 and 36 mg per kg body weight of a crude cephalin prepared from rat brain were suspended in saline and injected intraperitoneally in rats. The influence on coagulation, platelet adhesiveness, antifibrinolytic activity and incidence of experimental venous thrombosis was studied.The following observations were made:1. The recalcification time of plasma was shortened maximally one hour after the injection, with gradual return to normal values. Normal recalcification time was obtained 24 hours after the injection of the lowest dose, whereas it was still slightly shortened after the higher doses.2. The number of adhesive platelets increased, whereas no antifibrinolytic activity was found.3. An increased incidence of experimental venous thrombosis was observed.Thus, there seems to be a relation between increased platelet adhesiveness, accelerated recalcification time and the tendency to venous thrombosis.